Influence of hydrogen on incipient plasticity in CoCrFeMnNi high-entropy alloy - Yang, Guanghui (2021)
The influence of hydrogen on the onset of plastic deformation in a CoCrFeMnNi high-entropy alloy (HEA) was examined through the analysis of the load at which first pop-in during spherical nanoindentation experiments occurs on hydrogen-charged and subsequently aged specimens. Results reveal that the dissolved hydrogen lowers the plastic flow resistance, indicated by the shear yield strength, τy, by modifying defect formation energies. Aging, subsequent to charging, leads to recovery of τy, but only partially. The results are discussed in terms of the vacancy-mediated dislocation nucleation, which is supported by the estimated activation volume for deformation.